2011
DOI: 10.1007/s11481-011-9324-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Molecular Evidence for a Feedback Interaction Between Morphine and HIV-1 Viral Proteins

Abstract: Morphine use and addiction is common among HIV infected individuals. There is an abundance of research supporting the effects of morphine and other mu opioid receptor (MOR) ligands, on the function of HIV-1 viral proteins and progression of HIV-1 viral infection to AIDS. On the other hand, there is much less research that investigates the possible effects of the persistent presence of HIV-1 viral proteins on the expression of the MOR and the analgesic and rewarding effects of MOR ligands such as morphine. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…In summary, the presence of HIV-1 viral proteins leads to a decrease in DA receptors (Liu et al, 2009) and may explain the behavioral evidence that indicates that HIV-1Tg rats are more prone to addiction (Chang & Connaghan, 2012;.…”
Section: Hiv-1 and The Dopaminergic Systemmentioning
confidence: 93%
See 4 more Smart Citations
“…In summary, the presence of HIV-1 viral proteins leads to a decrease in DA receptors (Liu et al, 2009) and may explain the behavioral evidence that indicates that HIV-1Tg rats are more prone to addiction (Chang & Connaghan, 2012;.…”
Section: Hiv-1 and The Dopaminergic Systemmentioning
confidence: 93%
“…Statistical and bioinformatics analyses of each brain region between the two strains revealed that immune response-related pathways are altered in the HIV-1Tg rat, with brain region differences, suggesting that the persistent presence of HIV viral proteins causes inflammation in the brain of the HIV-1Tg rat (Li et al, 2013). In addition, analysis of serum cytokine levels revealed that, while LPS induces a significant increase in tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta in both F344 and HIV-1Tg rats, the increase in these cytokines was significantly greater in the HIV-1Tg rats (Chang & Connaghan, 2012;Rao et al, 2011).…”
Section: Brain-immune Interactions: Induction Of Neuroinflammation Bymentioning
confidence: 99%
See 3 more Smart Citations